Methylergometrine maleate from synchrotron powder diffraction data - Rohlíček, Jan (International Union of Crystallography, 2009)
The title compound {systematic name: 9,10-didehydro-N-[1-(hydroxymethyl)propyl]-d-lysergamide maleate}, C(20)H(26)N(3)O(2) (+)·C(4)H(3)O(4) (−), contains a large rigid ergolene group. This group consists of an indole plane connected to a six-membered carbon ring adopting an envelope conformation and N-methyltetrahydropyridine where the methyl group is in an equatorial position. In the crystal, intermolecular N—H⋯O, O—H⋯N and O—H⋯O hydrogen bonds form an extensive three-dimensional hydrogen-bonding network, which holds the cations and anions together.